Multi-institutional Comparison of Helicopter Transfers Directly to the Operating Room versus the Pit Stop in the Emergency Department. Issue 9 (September 2013) - Van Der Wilden, Gwendolyn M.; Janjua, Sumbal; Wedel, Suzanne K.; Agarwal, Suresh; Shapiro, Mark L.; Andersen, Nicholas D.; Odom, Stephen R.; Gates, Jonathan D.; Frakes, Michael A.; Chang, Yuchiao; Velmahos, George C.; Alam, Hasan B.; et al.
Presented September 24, 2011, at the 92 nd annual meeting of the New England Surgical Society, September 23–25, 2011, Mt. Washington, New Hampshire.